Synthesis, structure, and photoluminescence properties of Ce3+ and Tb3+ doped alkaline-earth silicate Sr2MgSi2O7 phosphors for WLEDs. Issue 3 (12th January 2017) - Wang, Yongqian; Chen, Yan; Sun, Qimeng; Yan, Bing
Abstract: Abstract : In this research, Ce 3+ and Tb 3+ doped alkaline-earth silicate Sr2 MgSi2 O7 phosphors have been synthesized by solid-state reaction. The results show that the Sr2− x MgSi2 O7 : x Ce 3+ phosphors exhibit a violet–blue emission with excitation at 348 nm, whereas the Sr2− y MgSi2 O7 : y Tb 3+ phosphor show a green emission with excitation at 243 nm. In addition, the structure of Sr2 MgSi2 O7 host has been analyzed by Crystalmaker program. Staggered arrangements of [SiO4 ] and [MgO4 ] units in the Sr2 MgSi2 O7 system underlie possible chemical tuning and phase segregation, providing a potential candidate of tunable luminescence. A red shift of wave length is clarified by crystal field theory and Van Uitert expression. The FESEM image of Sr1.99 MgSi2 O7 :0.01Ce 3+ phosphors reveal that it has a proper particle size for application in WLEDs. With different Tb 3+ doping concentration, the CIE chromaticity coordinates Sr2 MgSi2 O7 :Tb 3+ phosphors still remain a steady position. These results indicate that Sr2− x MgSi2 O7 : x Ce 3+, Sr2− y MgSi2 O7 : y Tb 3+ phosphors are promising phosphors for WLEDs.